(untitled) (New York, 2001)
Read by millions of students over seven editions, The Norton Anthology of English Literature remains the most trusted undergraduate survey of English literature available and one of the most successful college texts ever published. Firmly grounded by the hallmark strengths of all Norton Anthologies—thorough and helpful introductory matter, judicious annotation, complete texts wherever possible—The Norton Anthology of English Literature, The Major Authors has been revitalized in this Eighth Edition through the collaboration between six new editors and six seasoned ones. Under the direction of Stephen Greenblatt, General Editor, the editors have reconsidered all aspects of the anthology to make it an even better teaching tool.
Keywords: English literature